Pengaruh Mekanisme Corporate Governance terhadap Innate Accruals Quality dan Discretionary Accruals Quality - Sari Atmini (Jurnal Aplikasi Manajemen, 2012)
The objectives of this research empirically are to examine the effects of independent commissioner and audit committee characteristics (number of member, competencies, independency and frequency of meeting), to discretionary accruals quality and innate accruals quality. The sample of this research was determined using purposive sampling method. There are 46 companies fulfill the criteria. Data were analyzed using multiple regression analysis. The results of this research show that independent commissioner and audit committee characteristics (number of member, competencies, independency and frequency of meeting) do not affect discretionary accruals quality and innate accruals quality.Keywords: independent commissioner, audit committee, discretionary accruals quality, innate accruals quality